Dampak Motivasi Terhadap Kinerja Karyawan Pada PT. Univar Limawarnane Surabaya - Dhya Nur Aysiya; Sugiharto Sugiharto; Aridha Prasetya; Bambang Karnain (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
The problem faced by the company PT. Univar Limawarnane Surabaya is that employee performance is not yet optimal. Reflected by the lack of optimal employee performance, namely: (1) Realization of sales of laboratory equipment is not in accordance with the targets set by the company; (2) The placement of employees is not in accordance with their competence; and (3) The workload given by the company exceeds employee capacity. As in the concept of preparing scientific work, this research aims to analyze the influence of motivation on the performance of PT employees. Univar Limawarnane in Surabaya. Meanwhile, the research sample taken was 31 people (employees), according to the size of the existing population, because the number of employees was relatively small. The data analysis technique used in this research is simple linear regression analysis. The results of the research show that there is a significant influence between motivation variables on the performance variables of PT employees. Univar Limawarnane Surabaya. This is proven t = 3.601 at Sig = 0.01 or tcount = 3.601 while t table = 2.045 This means that motivation variables can be used as a basis for predicting the performance of PT employees. Univar Limawarnane Surabaya. This shows that the hypothesis proposed is supported by the data.